NATURAL BIOMATERIALS FOR SKIN TISSUE ENGINEERING: REPAIR AND REGENERATION - A SHORT REVIEW - L, Gowrisankar; J, Ganesh Murali; P, Usha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
The development of new materials and the enhancement of existing materials to develop skin regeneration are wide areas of research in polymeric biomaterials. The paper presents the analysis of a wide range of several natural polymers such as proteins and polysaccharides which can be utilized for skin tissue repair and regeneration. The reviews look at the few examples of commercially available natural - origin polymers with applications in tissue engineering. Natural polymers, such as proteins and polysaccharides, being components of, or structurally similar to, the glycosaminoglycans in the extracellular matrix (ECM) are valuable materials for tissue engineering applications. Natural polymers have great coincidence to natural ECM elements, particularly in biocompatibility and biodegradability. In this paper, the attention is focused on several natural polymers that found application in research work for drug or cell delivery within the skin tissue engineering field, namely collagen, chitin, chitosan, alginate, gellan, gelatin, and curcumin.